Completion surgery after extracapsular dissection of low-grade parotid gland malignant tumors - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Goncalves, Miguel; Koch, Michael; Iro, Heinrich (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2019)
Background: The aim of the study was to compare the oncological and functional outcome between extracapsular dissection and completion surgery on the one hand and sole extracapsular dissection on the other hand in small low-grade malignant parotid tumors. Methods: The records of all patients treated for T1-T2 low-grade malignant tumors of the parotid gland primarily by means of extracapsular dissection between 2006 and 2015 were studied retrospectively. Results: Forty patients with T1-T2 low-grade parotid malignancies were detected. Our study showed outstanding oncological outcomes in both patient groups, the facial nerve function being significantly better after sole extracapsular dissection in the direct postoperative phase, with no differences between the groups in the long term. Conclusions: Our study showed very encouraging preliminary results following primary extracapsular dissection as the sole surgical therapy for carefully selected low-stage, low-grade, inferiorly located lesions in patients with high compliance.
CRIS-Team Scopus Importer:2019-07-16
Keywords: extracapsular dissection; facial nerve; low-grade; malignant tumor; parotid gland

Confocal laser endomicroscopy of head and neck squamous cell carcinoma: a systematic review Konfokale Laser-Endomikroskopie des Kopf-Hals-Plattenepithelkarzinoms: eine systematische Übersicht - Sievert, Matti; Auberville, Marc; Oetter, Nicolai; Stelzle, Florian; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (Laryngo-Rhino-Otologie, 2021)
Objective: Confocal laser endomicroscopy (CLE), with a magnification of up to 1000 ×, offers the possibility to visualize intercellular spaces in vivo. CLE has already established itself in different disciplines. This article gives an overview of the current research on CLE in the diagnosis of the head and neck squamous cell carcinoma. Material and methods: Material and methods: Systematic bibliographic research in the following online databases: PubMed, MEDLINE, Thompson Reuters Web of Science, SPIE using the following keywords: confocal laser endomicroscopy, CLE, endomicroscopy, head and neck, larynx. Evaluation of the scientific relevance according to defined criteria. Results: All studies were analyzed concerning the clinical application, clinical findings, and computer-aided data processing. Conclusions: The recently published data suggest that CLE has a high potential to improve the diagnosis of malignant mucosal lesions in the upper aerodigestive tract.
CRIS-Team Scopus Importer:2021-01-22
Keywords: CLE; confocal laser endomicroscopy; head and neck malignancy; image analysis; laryngeal carcinoma

Deep learning-based detection of motion artifacts in probe-based confocal laser endomicroscopy images. - Aubreville, Marc; Stöve, Maike; Oetter, Nicolai; Goncalves, Miguel; Knipfer, Christian; Neumann, Helmut; Bohr, Christopher; Stelzle, Florian; Maier, Andreas (International Journal of Computer Assisted Radiology and Surgery, 2019)
Probe-based confocal laser endomicroscopy (pCLE) is a subcellular in vivo imaging technique capable of producing images that enable diagnosis of malign structural modifications in epithelial tissue. Images acquired with pCLE are, however, often tainted by significant artifacts that impair diagnosis. This is especially detrimental for automated image analysis, which is why said images are often excluded from recognition pipelines. We present an approach for the automatic detection of motion artifacts in pCLE images and apply this methodology to a data set of 15 thousand images of epithelial tissue acquired in the oral cavity and the vocal folds. The approach is based on transfer learning from intermediate endpoints within a pre-trained Inception v3 network with tailored preprocessing. For detection within the non-rectangular pCLE images, we perform pooling within the activation maps of the network and evaluate this at different network depths. We achieved area under the ROC curve values of 0.92 with the proposed method, compared to 0.80 for the best feature-based machine learning approach. Our overall accuracy with the presented approach is 94.8%. Over traditional machine learning approaches with state-of-the-art features, we achieved significantly improved overall performance. PURPOSE METHODS RESULTS CONCLUSION

Does increasing the incidence of extracapsular dissection for benign tumors of the parotid correlate with an increased need for revision surgery? - Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Goncalves, Miguel; Schapher, Mirco; Koch, Michael; Iro, Heinrich (Oral Oncology, 2019)
Objectives: The aim of this study was to investigate the hypothesis of whether extracapsular dissection (ED) of the parotid gland increases the need for revision surgery for benign tumours in comparison to traditional surgical modalities. A further aim of this study was to evaluate and compare the functional outcome of revision procedures after primary ED with other modalities involving the parotid gland in our department.
CRIS-Team WoS Importer:2019-06-21

Erratum: Correction: Confocal laser endomicroscopy of head and neck squamous cell carcinoma: a systematic review (Laryngo- rhino- otologie (2021) 100 11 (875-881)) Erratum: Konfokale Laser-Endomikroskopie des Kopf-Hals-Plattenepithelkarzinoms: eine systematische Übersicht - Sievert, Matti; Aubreville, Marc; Oetter, Nicolai; Stelzle, Florian; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (Laryngo-Rhino-Otologie, 2021)
CRIS-Team Scopus Importer:2024-12-16

Evaluation of preoperative Ultrasonography in the Differentiation between Superficial and Deep Parotid Gland Tumors - Mantsopoulos, Konstantinos; Tschaikowsky, Nastasja; Goncalves, Miguel; Müller, Sarina Katrin; Iro, Heinrich (Ultrasound in Medicine and Biology, 2020)
Imaging of the intraparotid course of the facial nerve remains a challenge and is not an established routine procedure. The aim of this study was to evaluate ultrasound in localizing a parotid tumor in relation to the facial nerve. The ultrasound findings and operative reports of all patients treated for parotid gland tumors were studied retrospectively. Eight hundred sixty-eight parotid lesions formed our study sample. The unit of measurement was the minimal distance between the parotideomasseteric fascia and the superficial capsule of the tumor, measured in millimeters by means of ultrasound. The mean value for this parameter was 1.3 mm for superficial and 4.6 mm for deep lobe tumors (p < 0.001). When the cutoff value was set at 2.6 mm, the sensitivity and specificity of ultrasound were 89.6 and 88.4%, respectively. Our study revealed that ultrasound can help in the pre-operative differentiation between tumors of the superficial and deep lobes of the parotid gland.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Deep lobe; Facial nerve; Parotid gland; Superficial lobe; Ultrasonography

Extracapsular dissection for warthin tumors despite the risk of ipsilateral metachronous occurrence - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Iro, Heinrich (Laryngoscope, 2018)
OBJECTIVES/HYPOTHESIS: The ideal extent of surgical intervention for cystadenolymphomas of the parotid gland remains a matter of controversy. The aim of our study was to assess the surgical outcome after extracapsular dissection for cystadenolymphomas of the parotid gland. A further purpose of this study was to examine how the number of primary cystadenolymphomas or the size of the primary lesion influences the possibility of an ipsilateral metachronous tumor occurrence. STUDY DESIGN: Retrospective clinical study. METHODS: A retrospective evaluation of the records was carried out for all patients treated for cystadenolymphomas of the parotid gland by means of extracapsular dissection at a tertiary referral center between 2000 and 2012. RESULTS: Three hundred twenty-seven patients were included in the study. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 3.1% (10/327) with a mean follow-up of 108.4 months. A significant difference in the rate of metachronous lesions between unilocular (1.7%) and multilocular (11.6%) tumors could be detected (χ2 (1) = 7.342, P < .001). Our analysis was not able to find any significant influence of the maximal tumor size on the rate of metachronous tumors (χ2 (1) = 0.634, P = .426). CONCLUSIONS: One of the most controversial issues in the treatment of cystadenolymphomas of the parotid gland concerns the question of which is the best therapeutic approach to be taken in such patients. Our analysis was able to demonstrate the benefits of extracapsular dissection in the management of solitary as well as carefully selected multicentric cystadenolymphomas with a consistently acceptable surgical outcome. LEVEL OF EVIDENCE: 4. Laryngoscope, 2521-2524, 2018.
EVALuna2:35386

Extracapsular Dissection in Pleomorphic Adenomas of the Parotid Gland: Results After 13 Years of Follow-up - Schapher, Mirco; Koch, Michael; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Laryngoscope, 2020)
Objectives/Hypothesis: To assess long-term results after the treatment of parotid pleomorphic adenomas (PPAs) using different surgical techniques and focusing on recurrence rates and the risk of adverse effects. Study Design: Retrospective analysis. Methods: Retrospective analysis of 182 patients treated exclusively for PPAs at a tertiary referral center between 2000 and 2004. Thorough follow-up examinations over a mean period of 13 years were possible in 53.8% (n = 98/182). Tumors were categorized according to the European Salivary Gland Society (ESGS) system to improve the comparison of outcomes. After different surgical resection strategies, recurrence rates, postoperative facial nerve paresis (FNP), and incidence of Frey's syndrome were assessed. The follow-up period included clinical examinations and imaging of every patient in the treating department. Results: Of 182 patients, extracapsular dissection (ED) was performed in 29.7%, and other surgical modalities (OSMs), including facial nerve dissection, in 70.3%. After the long-term follow-up, 98% of all the patients (n = 96/98) were recurrence free. When recurrence rates were compared, no significant differences were noted (P <.331). ED resulted in significantly lower FNP rates compared to OSMs (P <.001). FNP rates significantly increased with size and location of the tumors according to ESGS categories (temporary and permanent FNP, P =.04). Surgical invasiveness corresponded to a significant increase in the incidence of Frey's syndrome (P <.001). Conclusions: ED was associated with the lowest complication rates, but not with a higher risk of recurrence, when compared with OSM in the long-term course. As ED can be performed in the majority of PPAs, it can be regarded as the treatment of choice whenever possible. Level of Evidence: 4 Laryngoscope, 2020.
CRIS-Team Scopus Importer:2020-05-22
Keywords: extracapsular dissection; facial nerve dissection; limited surgery; Parotid pleomorphic adenoma; recurrence

Feasibility of intraoperative assessment of safe surgical margins during laryngectomy with confocal laser endomicroscopy: A pilot study - Sievert, Matti; Oetter, Nicolai; Aubreville, Marc; Stelzle, Florian; Maier, Andreas; Eckstein, Markus; Mantsopoulos, Konstantinos; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Koch, Michael; Agaimy, Abbas; Iro, Heinrich; et al. (Auris Nasus Larynx, 2021)
Objective: This pilot study aimed to assess the feasibility of intraoperative assessment of safe margins with Confocal Laser Endomicroscopy (CLE) during planned partial or total laryngectomy. Methods: Eight patients with confirmed larynx squamous cell carcinoma (SCC) and planned partial or total laryngectomy were included in this study in March 2020. Two head and neck surgeons and one pathologist were asked to classify carcinoma or healthy epithelium in a sample of 94 representative sequences (5.640 images), blinded to the histological results (H&E staining). Results: Healthy mucosa areas showed epithelium with cells of uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE optical biopsy of SCC demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 80.1%, 72.3%, 87.9%, 85.7%, and 76.1%, respectively. A distinct transition between healthy appearing tissue and suspicious lesions could also be detected. Conclusion: CLE can be easily integrated into the intraoperative setting, generate real-time, in-vivo microscopic images of the larynx for evaluation and demarcation of cancer. If validated in further studies, CLE could eventually contribute to a less radical approach by enabling a more precise evaluation of the cancer margin.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Confocal laser endomicroscopy; Laryngeal cancer; Safe surgical margins

Feasibility of sentinel lymph node detection by near-infrared endoscopy in squamous cell carcinoma of the oral cavity: A pilot study - Sievert, Matti; Goncalves, Miguel; Eckstein, Markus; Iro, Heinrich; Koch, M. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: Near-Infrared (NIR) fluorescence imaging is a novel technique for intraoperative sentinel lymph node (SLN) identification. It has demonstrated promising results in several surgical specialties. The study aims to evaluate the feasibility of identifying the SLN by indocyanine green (ICG) enhanced NIR endoscopy in squamous cell carcinoma of the oral cavity (OCSCC). PATIENTS AND METHODS: Seven patients with (cT1-3 N0) OCSCC were included. We injected 1-1.25 ml of ICG (5 mg/ml) at four to five points around the primary. After the elevation of a platysma flap and posterior retraction of the sternocleidomastoid muscle, fluorescence images were taken via IMAGE1 STM NIR/ICG system to define the SLN(s). We sampled fluorescence marked SLN(s) stratified to lymph node levels, followed by level-specified elective neck dissection. RESULTS: The detection of at least one unilateral or bilateral SLN (range 1-5) was possible in every case. The fluorescence signal occurred, on average, 5.0 ± 2.2 minutes after injection. A total of 22 SLN could be identified. Among 331 histo-logically examined lymph nodes we could detect one micrometastasis, which was correctly defined as SLN (1/22). There were no false-negative findings. No adverse reactions to ICG occurred. CONCLUSIONS: Our first results are indicating the concept of SLN concerning OCSCC after the application of real-time NIR fluorescence endoscopy. However, this has to be verified by more extended studies.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Indocyanine green; Near-infrared-imaging; Neck dissection; Oral cavity squamous cell carcinoma; Sentinel node biopsy

Going beyond extracapsular dissection in cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Koch, Michael; Traxdorf, Maximilian; Schapher, Mirco; Iro, Heinrich (Oral Oncology, 2019)
BACKGROUND: The aim of this study was to evaluate the potential for reducing surgical invasiveness in parotid cystadenolymphomas by means of capsular dissection based on the experience made in our department and on various aspects of these lesions gained from the relevant literature. METHODS: All patients treated for cystadenolymphomas with extracapsular or capsular dissection at a tertiary referral center between 2000 and 2017 were examined retrospectively. A literature review of various aspects and of different treatment strategies for this lesion was also performed. RESULTS: 629 patients were included in the study. 499 had solitary tumors (79.3%) and 130 had unilateral multicentric lesions (20.7%). 595 patients were managed by means of ED, while 34 patients underwent a CD. Our analysis detected an overall occurrence rate of ipsilateral metachronous tumors of 2.06% (13/629), all after extracapsular dissection, with a mean follow-up of 104.1 months. No statistical difference could be found between ED and CD in the overall occurrence rate of ipsilateral metachronous tumors or in the complication rate. No cases of a malignancy arising from a preexisting Warthin tumor could be detected in our study sample. CONCLUSION: A clear potential for reducing surgical invasiveness could be shown. A reliable imaging diagnosis, appropriate patient counseling and high compliance with close follow-up are the basic prerequisites for an acceptable outcome.
EVALuna2:35382

Hydroxyapatite bone cement in the reconstruction of defects of the long process of the incus: Personal experience and literature review - Mantsopoulos, Konstantinos; Thimsen, Vivian; Wohlleben, Felix; Sievert, Matti; Müller, Sarina Katrin; Goncalves, Miguel; Iro, Heinrich; Hornung, Joachim; Taha, Lava (American Journal of Otolaryngology, 2021)
Objective: Erosion of the long process of the incus is the most common ossicular chain pathology occurring in the course of chronic middle ear disease. The aim of this study was to evaluate our experience in the reconstruction of short-length defects of the long process of the incus using hydroxyapatite bone cement over a period of 15 years. Methods: The medical records of all patients treated with hydroxyapatite bone cement for an isolated short-length erosion of the long process of the incus or the lenticular process at an academic tertiary referral center between 2005 and 2019 were studied retrospectively. Results: 48 patients made up our study sample (19 men, 29 women). The mean age at the time of surgery was 38.1 years. The mean preoperative air-bone gap (ABG) was 21.36 dB. The mean postoperative ABG was 15.89 dB within 8 weeks of surgery and 11.81 dB at least 6 months after surgery. The postoperative ABG had significantly improved compared to preoperative ABG values at both the short- and middle-term follow-up (p < 0.001 for both). An ABG ≤ 20 dB was achieved in 68% in the short term and 83% in the middle term. The mean ABG in the long term (< 12 months) was 11.1 dB. Conclusion: Restoration of the anatomic and functional continuity of the ossicular chain using hydroxyapatite cement in defects of the long process of the incus seems to warrant a satisfactory audiologic outcome in the majority of cases.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Bone cement; Hydroxyapatite; Incus; Long process; Ossicular chain

Impact of delayed adjuvant therapy after surgery in p16 positive oropharyngeal cancer: a retrospective analysis - Sievert, Matti; Goncalves, Miguel; Müller, Sarina Katrin; Hecht, M.; Pflaum, A.; Grundtner, P.; Iro, H.; Gostian, A. O.; Iro, Heinrich (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: This study aimed to clarify the impact of delayed adjuvant therapy on the outcome of HPV associated oropharyngeal squamous cell carcinoma (HPV-OPSCC). PATIENTS AND METHODS: A total of 157 patients with HPV-OPSCC treated by surgery and adjuvant radiotherapy or chemoradiation therapy were analyzed retrospectively. We divided participants into two groups implementing adjuvant therapy within or after 50 days. Primary endpoints were the rates of locoregional recurrence and distant metastases, overall survival, and disease-specific survival. RESULTS: Adjuvant treatment began within 50 days (average: 38.8 days) in 79 cases compared to 78 cases after 50 days (average: 71.5 days). Five-year overall survival was 85.7% and 87.4% (p=0.588), the rates of local and regional recurrence were 3.8% and 6.4% (p=0.455) and of distant metastases 5.1% and 9% (p=0.369) implementing adjuvant treatment within or later than 50 days, respectively. CONCLUSIONS: These results suggest that adjuvant therapy initiated later than seven weeks after primary ablative surgery may still be effective HPV-OPSCC.
CRIS-Team Scopus Importer:2020-03-06

Impact of intraepithelial capillary loops and atypical vessels in confocal laser endomicroscopy for the diagnosis of laryngeal and hypopharyngeal squamous cell carcinoma - Sievert, Matti; Eckstein, Markus; Mantsopoulos, Konstantinos; Müller, Sarina Katrin; Stelzle, Florian; Aubreville, Marc; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose Confocal laser endomicroscopy (CLE) allows surface imaging of the laryngeal and pharyngeal mucosa in vivo at a thousand-fold magnification. This study aims to compare irregular blood vessels and intraepithelial capillary loops in healthy mucosa and squamous cell carcinoma (SCC) via CLE.
CRIS-Team WoS Importer:2021-07-23

Influence of p16 status on indication and outcome of salvage neck dissection in oropharyngeal cancer - Müller, Sarina Katrin; Mantsopoulos, Konstantinos; Semrau, Sabine; Agaimy, Abbas; Eckstein, Markus; Traxdorf, Maximilian; Gostian, Antoniu Oreste; Goncalves, Miguel; Sievert, Matti; Haderlein, Marlen; Grundtner, Philipp; Hecht, Markus; et al. (Acta Oto-Laryngologica, 2020)
Background: Human papillomavirus (HPV)+ and HPV– oropharyngeal squamous cell carcinomas (OPSCC) are separate tumor entities. Aims/Objectives: The aim of this study was to examine if the p16 status influences the need and outcome of a salvage neck dissection (SND) after primary radiochemotherapy (pRCT). Material and methods: Retrospective study of 164 patients (n = 108 p16–, n = 56 p16+) who underwent pRCT for OPSCC between 2009 and 2016. HPV status was defined via p16 immunohistochemical staining. Clinical nodal status was assessed using ultrasound and computed tomography of the neck with contrast. Results: Of the 56 p16+ patients, 17 (30.4%) patients were given an indication for a SND after pRCT with 4 (23.5%) patients showing persistent malignant nodes. Of the 108 p16– patients, 24 (22.2%) patients underwent a SND with 8 (33.3%) patients showing persistent malignant nodes. There was no significant association of the p16 status and neither the indication for SND (p(Chi2(two-sided)-Test) = 0.25, ϕ = 0.34) nor the occurrence of positive nodes (p(Chi2(two-sided)-Test) = 0.74, ϕ = 0.50). The probability for persistence of the ypN + nodal status independent of HPV-status was 29.2%(12/41). Conclusions and significance: There was neither a significant association between the p16 status and the indication for a SND nor for persistent malignant nodal disease after pRCT.
CRIS-Team Scopus Importer:2020-11-06
Keywords: de-escalation; HPV; Oropharyngeal cancer; p16; radiochemotherapy

Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Zenk, Johannes; Bozzato, Alessandro; Kuenzel, Julian; Zengel, Pamela; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
Purpose The aim of this study was to assess the interrater reliability of ultrasound for diagnosing sialolithiasis. Materials and Methods A total of 100 consecutive patients with signs of obstructive sialadenopathy were evaluated. The patients all underwent ultrasound examinations in a standardized manner conducted by one specialist with extensive experience in the management of salivary gland disorders and proficiency in head and neck ultrasonography. The video recordings were sent to six colleagues with comparable experience without providing any further information about the patients' medical history and physical examination. Results The overall agreement between the seven observers was substantial, with a κ of 0.765 for the 100 cases and a percentage agreement level of 88.29 ± 3.01 % (range: 83-94 %). The range of agreement on this video set for observer pairs varied from substantial to almost perfect agreement (0.663 to 0.878). Among the few false-negative findings (5.4 %), 71.8 % were due to distal sialolithiasis. Two-thirds of the false-positive findings (3.7 %) were due to fibrotic stenosis. Conclusion The study confirmed the diagnostic value of ultrasound in sialolithiasis and demonstrated a very high level of interrater agreement, even in the absence of additional clinical patient information, thus further underscoring the importance of ultrasound as the examination of first choice in sialolithiasis.
CRIS-Team Scopus Importer:2019-08-16
Keywords: interrater; parotid; sialolithiasis; submandibular; ultrasound

Intraductal Pneumatic Lithotripsy after Extended Transoral Duct Surgery in Submandibular Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Otolaryngology-Head and Neck Surgery, 2018)
Objective Persistent, residual, or recurrent stones after transoral duct surgery are always associated with hilar to intraparenchymal and/or multiple sialolithiasis, causing difficulties in the treatment. This study was performed to assess the value of intraductal lithotripsy in the treatment of persistent, residual, or recurrent sialolithiasis after extended duct surgery in the submandibular gland. Study Design Retrospective study covering February 2015 to June 2018. Study Setting Tertiary referral center for salivary gland diseases. Subjects and Methods After extended ductal surgery, 39 patients presenting with persistent, residual, or recurrent stones were treated. Four patients had persistent stones; 16 had residual stones; and 19 presented with recurrent stones. Among these patients, 50 stones were treated with intraductal pneumatic lithotripsy. Fragmentation rate, stone-free rate, and symptom-free rate after treatment with intraductal lithotripsy were outcome measures. Results Of the 39 patients, 97.4% became stone-free, and all were symptom-free. Ninety-eight percent of the stones were completely fragmented. For 23.1% of the patients, >1 stone was treated with intraductal lithotripsy. All patients with persistent stones, 93.7% of those with residual stones, and all with recurrent stones became stone-free and symptom-free. No severe complications developed. Conclusions This study shows that patients presenting with difficult and/or multiple sialolithiasis after extended transoral submandibular duct surgery can be treated with success rates >97%. For multiple sialolithiasis in particular, a multimodal treatment approach with interventional sialendoscopy and intraductal lithotripsy as a central element is a prerequisite for success, as this enables the most difficult part to be performed with high success rates.
EVALuna2:35383

Intraoperative free margins assessment of oropharyngeal squamous cell carcinoma with confocal laser endomicroscopy: a pilot study - Sievert, Matti; Stelzle, Florian; Aubreville, Marc; Müller, Sarina Katrin; Eckstein, Markus; Oetter, Nicolai; Maier, Andreas; Mantsopoulos, Konstantinos; Iro, Heinrich; Goncalves, Miguel (European Archives of Oto-Rhino-Laryngology, 2021)
Purpose: This pilot study aimed to assess the feasibility of intraoperative assessment of safe margins with confocal laser endomicroscopy (CLE) during oropharyngeal squamous cell carcinoma (OPSCC) surgery. Methods: We included five consecutive patients confirmed OPSCC and planned tumor resection in September and October 2020. Healthy appearing mucosa in the marginal zone, and the tumor margin, were examined with CLE and biopsy during tumor resection. A total of 12,809 CLE frames were correlated with the gold standard of hematoxylin and eosin staining. Three head and neck surgeons and one pathologist were asked to identify carcinoma in a sample of 169 representative images, blinded to the histological results. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE optical biopsy of OPSCC demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 86%, 90%, 79%, 88%, and 82%, respectively, with inter-rater reliability and κ-value of 0.60. Conclusion: CLE can be easily integrated into the intraoperative setting, generate real-time, in-vivo microscopic images of the oropharynx for evaluation and demarcation of cancer. It can eventually contribute to a less radical approach by enabling a more precise evaluation of the cancer margin.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Confocal laser endomicroscopy; Head and neck malignancies; Oropharyngeal squamous cell carcinoma; Safe surgical margins

Investigation of the surgical strategies for unilateral multifocal cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Goncalves, Miguel; Iro, Heinrich (Oral Oncology, 2018)
OBJECTIVES: The aim of the study was to compare multifocal extracapsular dissection with complete parotidectomy in the treatment of unilateral multifocal cystadenolymphomas of the parotid gland. MATERIALS AND METHODS: The records from all patients treated for unilateral multifocal cystadenolymphomas of the parotid gland at a tertiary referral center between 2000 and 2016 were retrospectively analyzed. RESULTS: 203 patients were included in the study. 96 patients were managed by multifocal extracapsular dissection, 107 patients underwent complete parotidectomy. Metachronous tumors were detected in 7 cases (3.4%) with a significant difference in the occurrence rate between multifocal extracapsular dissection (7/96, 7.3%) and complete parotidectomy (0/107, 0%) (p = 0.004). Permanent facial palsy was significantly more common after complete parotidectomy (21/107, 19.6%) than multifocal extracapsular dissection (2/96, 2.1%) (p = 0.000). CONCLUSIONS: The functional benefit of multifocal extracapsular dissection was counterbalanced by the advantage of complete parotidectomy, in terms of recurrences. Extracapsular dissection is at its limit in cases of multifocal cystadenolymphomas and the indication for it should be thoroughly verified in each and every case.
EVALuna2:35388

Long-term follow-up as an indispensable parameter for reliable assessment of the audiologic outcome after middle ear surgery - Mantsopoulos, Konstantinos; Thimsen, Vivian; Goncalves, Miguel; Sievert, Matti; Müller, Sarina Katrin; Iro, Heinrich; Hornung, Joachim (American Journal of Otolaryngology, 2021)
CRIS-Team WoS Importer:2021-10-22

Long-term oncologic and functional outcome in pleomorphic adenomas of the submandibular gland - Mantsopoulos, Konstantinos; Goncalves, Miguel; Schapher, Mirco; Iro, Heinrich (Laryngoscope, 2017)
Objectives: The aim of the study was to evaluate the oncologic and functional long-term outcome after surgical therapy of pleomorphic adenomas of the submandibular gland. Methods: The medical charts of all patients treated for pleomorphic adenomas of the submandibular gland by means of submandibulectomy between 2000 and 2016 were studied retrospectively. Patients who had had revision after external primary surgery, as well as patients with insufficient data were excluded from our study sample. Results: A total of 75 patients formed our study sample (28 men, 47 women, male:female ratio 0.59:1). Their mean age was 48 years (14-78 years). Mean follow-up was 82 months (12-170 months). No recurrences of a pleomorphic adenoma could be detected in our study cases. Normal facial nerve function (House-Brackmann grade I) in the direct postoperative phase was shown in 54/75 cases (72%). In the remaining 21/75 cases (28%), mild paresis of the marginal mandibular branch of the facial nerve (House-Brackmann II) could be detected in the direct postoperative phase. All cases with facial palsy had recovered with normal facial nerve function (House-Brackmann I) in 3-6 months. Conclusion: Our study was able to show oncologic and consistently acceptable oncologic and functional outcomes after submandibulectomy for pleomorphic adenomas of the submandibular gland. Level of Evidence: 4.
EVALuna2:33360

Multimodal treatment in difficult sialolithiasis: Role of extracorporeal shock-wave lithotripsy and intraductal pneumatic lithotripsy - Schapher, Mirco; Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; von Scotti, Felix; Goncalves, Miguel; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES: To assess results after treatment of difficult/complex sialolithiasis with extracorporeal shock-wave lithotripsy (ESWL) and intraductal pneumatic lithotripsy (IPL). STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: Altogether, 63 stones were diagnosed in 38 patients with difficult/complex sialolithiasis. Forty-nine stones were treated with fragmentation using both ESWL and IPL. Stones accessible with the sialendoscope were treated primarily with IPL in multiple sialolithiasis. RESULTS: Seventy-one ESWL procedures and 57 IPL were performed in our patients. Forty-nine stones were treated by 67 ESWL procedures and 52 IPL. ESWL converted sialoliths from sialendoscopically untreatable into sialendoscopically treatable cases in 94.7%; the treatment then was completed by a total of 52 IPL procedures. ESWL was performed before IPL (81.6%), in combination with IPL (7.9%) and after (10.5%). Complete fragmentation was achieved in 97.9%. Four stones each were treated with ESWL and IPL alone in multiple sialolithiasis. Altogether, 53 stones were treated by 57 IPL procedures. Complete fragmentation was achieved in 98.1% of the 53 stones. ESWL and IPL were the dominant treatment modalities in 84.1% of all 63 stones treated. Of all 38 patients, 92.1% became stone-free and all became symptom-free. All the glands were preserved. Multiple stones were treated in 34.2% of the patients; of these, 92.3% became stone-free. CONCLUSION: These results show that patients with difficult and complex sialolithiasis can be treated with high success rates of > 90% using a multimodal, minimally invasive, and gland-preserving treatment approach. ESWL and IPL played a key role in this multimodal treatment regime in > 80% of stones. LEVEL OF EVIDENCE: 4. Laryngoscope, 2017.
EVALuna2:33362

Outcomes of transoral laser microsurgery and transoral robotic surgery in oropharyngeal squamous cell carcinoma - Sievert, Matti; Goncalves, Miguel; Zbidat, Ali; Traxdorf, Maximilian; Müller, Sarina Katrin; Iro, Heinrich; Gostian, Antoniu Oreste (Auris Nasus Larynx, 2020)
Objective: Transoral robotic surgery (TORS) has evolved to a standard therapy modality for oropharyngeal carcinoma, especially in T1/ T2 tumors involving the base of the tongue due to its advantages compared with open surgery. However, knowledge about its benefits compared with transoral laser microsurgery (TLM) are scarce. This study compares oncological and functional results of TLM or TORS in the treatment of oropharyngeal squamous cell carcinoma (OPSCC). Methods: This retrospective analysis comprises all patients with OPSCC treated with TLM (n = 30) or TORS (n = 24) between April 2003 and May 2018 (follow-up 43 ± 38.3 months). Both treatment groups (TLM and TORS) were comparable in terms of the stage of the disease, prognosis-determining factors, and adjuvant therapy modalities. Results: There were no significant differences regarding to the resection status (p = 0.272), the rate of local- (p = 0.834) and distant- recurrence (p = 0.416), with a disease-free survival of 86.7 % and 87.5 %, respectively (p = 0.892). In addition, we could not confirm any differences regarding to operating time (p = 0.860), intraoperative blood loss (p = 0.660), inpatient stay (p = 0.585) and postoperative bleeding rate (p = 0.245). The frequency of tracheostomy and percutaneous endoscopic gastrostomy between both groups is comparable, with a longer duration of tube feeding in patients who have received TLM (p = 0.030). Conclusion: In conclusion, TORS allows for similar oncological outcomes compared with TLM at comparable perioperative risks. The postoperative swallowing function may benefit from TORS.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Head and neck cancer; Oropharyngeal cancer; Primary ablative surgery; Transoral laser microsurgery; Transoral robotic surgery

Papillary stenosis of the submandibular gland caused by dental prostheses - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology, 2020)
Objectives: The aim of this study was to assess diagnosis and treatment of submandibular duct stenosis caused by dental prostheses. Study Design: This retrospective study included 9 patients with papillary stenosis caused by physical irritation of the Wharton duct ostium by a mandibular dental prosthesis. Diagnostics included physical examination, as well as transcutaneous and transoral ultrasound examinations. Treatment consisted of duct incision, papillotomy, and subsequent sialendoscopy. After surgery, patients were advised to have the dental prosthesis altered by the dentist and to have regular gland massage. Follow-up data were obtained via telephone interviews. The most important outcome parameter was a symptom-free state. Results: In all 9 patients, the insertion of the sialendoscope was initially impossible because of the stenosis. After duct incision, sialendoscopy ruled out other obstructive causes and inflammatory states, leaving the dental prosthesis as the only underlying cause of the obstruction. Seven of the 9 treated patients were interviewed after a follow-up period of 28.1 (± 25.4) months. The procedures had resulted in all patients being symptom-free, without any reported complications. Conclusions: Mandibular prostheses can cause stenosis of the papillary region with subsequent submandibular duct obstruction. Surgical therapy is easy to perform and results in excellent long-term outcomes.
CRIS-Team Scopus Importer:2020-03-06

Parotid pleomorphic adenomas: Factors influencing surgical techniques, morbidity, and long-term outcome relative to the new ESGS classification in a retrospective study - Schapher, Mirco; Koch, Michael; Agaimy, Abbas; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Journal of Cranio-Maxillofacial Surgery, 2019)
Purpose: To assess long-term results after treatment of parotid pleomorphic adenomas (PPAs) with different surgical techniques, standardized according to the European Salivary Gland Society (ESGS) classification system. Methods: We analyzed ESGS categories, occurrence of facial nerve paresis (FNP), Frey's syndrome, histopathology, and recurrences. Surgical modalities were compared, differentiating techniques with and without facial nerve dissection. A strict protocol ensured a postoperative follow-up-period of more than 7 years. Results: 205 patients were included. A complete follow-up was possible in 138 patients, 77 of whom underwent extracapsular dissection (ED) and 61 of whom had other surgical modalities (OSMs). ESGS categories correlated with the extent of surgery, significantly with the risk for FNP and Frey's syndrome, but not with recurrences. Recurrences did not differ significantly between ED and OSMs, whereas the risks for FNP (p < 0.001 each) and Frey's syndrome (p = 0.000) were significantly higher after OSMs in comparison with ED. Young women with a stroma-rich (myxoid) tumor subtype appear to have the greatest risk for recurrences. Conclusion: ED is the treatment of choice for PPAs, if possible, resulting in similar recurrence rates but significantly fewer comorbidities in comparison with more extensive surgery. After the treatment of PPAs, a long-term follow-up is needed, including imaging.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Extracapsular dissection; Facial nerve paresis; Follow-up; Frey's syndrome; Pleomorphic adenoma; Recurrence

Patch-based Carcinoma Detection on Confocal Laser Endomicroscopy Images - A Cross-Site Robustness Assessment - Aubreville, Marc; Goncalves, Miguel; Knipfer, Christian; Oetter, Nicolai; Würfl, Tobias; Neumann, Helmut; Stelzle, Florian; Bohr, Christopher; Maier, Andreas (Proceedings of the 11th International Joint Conference on Biomedical Engineering Systems and Technologies (BIOSTEC 2018), 2018)
Deep learning technologies such as convolutional neural networks (CNN) provide powerful methods for image recognition and have recently been employed in the field of automated carcinoma detection in confocal laser endomicroscopy (CLE) images. CLE is a (sub-)surface microscopic imaging technique that reaches magnifications of up to 1000x and is thus suitable for in vivo structural tissue analysis. In this work, we aim to evaluate the prospects of a priorly developed deep learning-based algorithm targeted at the identification of oral squamous cell carcinoma with regard to its generalization to further anatomic locations of squamous cell carcinomas in the area of head and neck. We applied the algorithm on images acquired from the vocal fold area of five patients with histologically verified squamous cell carcinoma and presumably healthy control images of the clinically normal contra-lateral vocal cord. We find that the network trained on the oral cavity data reaches an accura

Pneumoparotid: Practical impact of Surgeon performed Ultrasound in an effective Diagnostic Approach - Goncalves, Miguel; Sievert, Matti; Mantsopoulos, Konstantinos; Schapher, Mirco; Müller, Sarina Katrin; Iro, Heinrich; Koch, Michael (Oral Diseases, 2022)
Objectives: Pneumoparotid is characterized by air inclusions in the parotid duct system. Use of ultrasound has proved valuable for evaluating air inclusions in various parts of the body; the diagnostics of this condition has not been systematically analyzed, however. The aim of this study was to evaluate the value of ultrasound in the detection of air inclusions along the parotid duct system and its closer characterization. Methods: Retrospective analysis was carried out of patients diagnosed with pneumoparotid between 2005 and 2020 in a salivary gland center. Ultrasound was performed in all cases, and features of air inclusions were described. Reference standard was the clinical demonstration of foamy saliva after gland massage and/or sialendoscopic evidence of intraductal air inclusions. Results: Twenty-one patients were identified (48.8 ± 3.8 years). Two were associated with wind instruments; seven were iatrogenic, following treatment for duct stenosis; one after radiotherapy; four with known bruxism and seven were idiopathic and without associated conditions. On ultrasound examination, pneumoparotid was characterized by three phenomena: flattened, mobile hyperechoic reflexes, dirty shadows with reverberation or “sunbeam effect,” and shifting shadows during gland massage. Conclusions: Ultrasound was useful for characterizing pneumoparotid in a fast and practical way and could serve as imaging tool of first choice.
CRIS-Team Scopus Importer:2022-07-15
Keywords: diagnostics; parotid gland; pneumoparotid; ultrasound

Postinflammatory Medial Meatal Fibrosis: Histopathologic Features and Outcomes of Surgical Management - Mantsopoulos, Konstantinos; Thimsen, Vivian; Müller-Hübner, Sarina Katrin Ursel; Sievert, Matti; Goncalves, Miguel; Iro, Heinrich; Agaimy, Abbas; Hornung, Joachim (Ent-Ear Nose & Throat Journal, 2021)
Objectives: The aims of our study were to investigate the clinical and audiometric outcome of the surgical treatment of postinflammatory medial meatal fibrosis (PIMMF) and to review the histopathologic changes in the specimens of the fibrotic plug, in order to try to shed light on the pathogenesis of the disease. Materials and Methods: The clinical records and the histopathologic specimens of all patients who underwent tympanomeatoplasty for PIMMF at the ENT Clinic of the University of Erlangen between 2006 and 2020 were evaluated retrospectively. Results: Thirty-four patients (41 primary surgical procedures) made up our study cohort. Of this, 28 cases were managed by means of meatoplasty and 13 cases with tympanomeatoplasty. The mean preoperative air–bone gap (ABG) was 27.8 dB (10-44 dB). Postoperative ABG was significantly improved compared to preoperative values at both short- and long-term follow-ups (P <.001 for both). No significant difference was noted between short-term and long-term ABG (P =.240). An ABG ≤20 dB was achieved in 65.8% of patients (short term) and 50% (long term). The overall rate of revision surgery for restenosis was 29.3% (12/41). Histopathologic reevaluation of the fibrotic plugs revealed a mosaic of patterns with frequent occurrence of secondary cholesteatoma-like lesions and keloid-like tissue changes. Lichenoid submucosal inflammation and increased ectopic ceruminous gland lobules were seen less frequently. Discussion: The moderate long-term outcome of surgical management and the identification of histologic changes with therapeutic implications might pave the way for alternative nonsurgical treatment options.
CRIS-Team Scopus Importer:2021-04-19
Keywords: air–bone gap; cholesteatoma; keloid; lichen; postinflammatory medial meatal fibrosis

Postoperative management of antithrombotic medication in microvascular head and neck reconstruction: a comparative analysis of unfractionated and low-molecular-weight heparin - Sievert, Matti; Goncalves, Miguel; Tamse, Rosalie; Müller, Sarina Katrin; Koch, Michael; Gostian, Antoniu Oreste; Iro, Heinrich; Scherl, Claudia (European Archives of Oto-Rhino-Laryngology, 2020)
Purpose: Free flap reconstruction is a valuable technique to preserve function in oncological head and neck surgery. Postoperative graft thrombosis is a dreaded risk. This study aims to compare low-dose unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) in perioperative thrombosis prophylaxis. Methods: This is a retrospective analysis of 266 free flaps performed at our academic center. A comparison was made between 2 patient groups, based on their respective postoperative prophylaxis protocols either with UFH (n = 87) or LMWH (n = 179). Primary endpoints were the frequency of transplant thrombosis and the number of flap failures. Secondary endpoints were the occurrence of peri- and postoperative complications. Results: The flap survival rate was 96.6% and 93.3% for the groups UFH and LMWH, respectively (P = 0.280). The rate of postoperative bleeding requiring revision was 4.6% and 6.7% for each group, respectively (P = 0.498). We found a hematoma formation in 4.6% and 3.9% (P = 0.792). Conclusion: The free-flap survival rate using low-dose UFH seems to be equivalent to LMWH regimens without compromising the postoperative outcome. Consequently, for risk-adapted thrombosis prophylaxis, either LMWH or UFH can be administrated.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Antithrombotic agent; Flap failure; Free-flap reconstruction; Head and neck; Thrombosis

Probe-based confocal laser endomicroscopy in detecting malignant lesions of vocal folds. - Goncalves, Miguel; Aubreville, Marc; Müller, Sarina Katrin; Sievert, Matti; Maier, Andreas; Iro, Heinrich; Bohr, Christopher (Acta Otorhinolaryngologica Italica, 2019)
Probe-based confocal laser endomicroscopy (CLE) is an innovative technique for real-time, non-invasive analysis of the surface epithelium. While being successfully used for diagnosis by experts, this method has not yet been established in clinical routine, partly due to the lack of standards and criteria for classifying various lesions. Our aim was to determine the diagnostic value and inter-rater reliability of CLE in detecting malignant lesions of the vocal cords. 58 video sequences were extracted from the probe-based CLE (GastroFlex probe with a Cellvizio® laser system) examinations of 3 patients with squamous cell carcinomas and 4 patients with benign alterations of the vocal folds. Two ENT surgeons, who were blinded to the histological result, were asked to identify the sequences representing a carcinoma. We showed an accuracy, sensitivity, specificity, PPV and NPV of 91.38-96.55%, 100%, 87.8-95.2%, 77.27-89.47% and 100%, respectively, with an inter-rater reliability of k = 0.89 ("almost perfect agreement"). Probe-based CLE is a promising method for diagnosis and assessment of vocal fold lesions in vivo. Our results suggest that, with adequate training, the diagnostic value of this technique can be improved and potentially provide important information during oncological surgery.

Response to Letter to the editor: Interrater Reliability of Ultrasound in the Diagnosis of Sialolithiasis: Methodological Issues. Interrater Reliability of Ultrasound: Methodological Issues - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Ultraschall in der Medizin, 2019)
CRIS-Team Scopus Importer:2019-10-18

Salvage laryngectomy after primary radio- and radiochemotherapy : A retrospective study - Sievert, Matti; Goncalves, Miguel; Binder, Benedicta; Müller, Sarina Katrin; Rupp, Robin; Koch, Michael; Dürr, Stephan; Traxdorf, Maximilian; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (HNO, 2021)
BACKGROUND: Recurrent and residual laryngeal cancer after organ-preserving radio- or radiochemotherapy is associated with a poor prognosis. Salvage surgery is the most important therapeutic option in these cases. OBJECTIVE: The study assessed rates of recurrence and residual tumor as well as survival and complication rates after salvage laryngectomy at the authors' academic cancer center. MATERIALS AND METHODS: A retrospective examination of all patients receiving laryngectomy between 2001 and 2019 due to tumor residuals or recurrence after primary radio- and radiochemotherapy was conducted. RESULTS: A total of 33 salvage procedures were performed. Defect reconstruction was performed by free flap surgery in 30.3% (n = 10) and regional flap surgery in 15.2% (n = 5) . One patient received regional flap surgery and free flap surgery simultaneously. Overall survival after 1, 2, and 5 years was 68.7, 47.9, and 24.2%, and disease-free survival was 81.6, 47.8, and 24.2%, respectively, with 48.5% (n = 16) postoperative tumor recurrences overall. Disease-free survival was significantly shorter for tumor extension into or onto the hypopharynx (p = 0.041). Postoperatively, 72.7% of patients developed a pharyngocutaneous fistula, of which 24.2% required surgical treatment. The hospital stay was 28.0 ± 16.1 days. CONCLUSION: Salvage laryngectomy is associated with a high rate of treatable complications and high morbidity. Nevertheless, considering the advanced tumor stages treated, it allows for respectable oncological results.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Laryngeal neoplasms; Postoperative complications; Recurrence; Salvage therapy; Treatment outcome

Salvage-Laryngektomie nach primärer Radio- und Radiochemotherapie: Eine retrospektive Fallzusammenfassung - Sievert, Matti; Goncalves, Miguel; Binder, Benedicta; Müller, Sarina Katrin; Rupp, Robin; Koch, Michael; Dürr, Stephan; Traxdorf, Maximilian; Hecht, Markus; Iro, Heinrich; Gostian, Antoniu-Oreste (HNO, 2021)
Background: Recurrent and residual laryngeal cancer after organ-preserving radio- or radiochemotherapy is associated with a poor prognosis. Salvage surgery is the most important therapeutic option in these cases. Objective: The study assessed rates of recurrence and residual tumor as well as survival and complication rates after salvage laryngectomy at the authors’ academic cancer center. Materials and methods: A retrospective examination of all patients receiving laryngectomy between 2001 and 2019 due to tumor residuals or recurrence after primary radio- and radiochemotherapy was conducted. Results: A total of 33 salvage procedures were performed. Defect reconstruction was performed by free flap surgery in 30.3% (n = 10) and regional flap surgery in 15.2% (n = 5). One patient received regional flap surgery and free flap surgery simultaneously. Overall survival after 1, 2, and 5 years was 68.7, 47.9, and 24.2%, and disease-free survival was 81.6, 47.8, and 24.2%, respectively, with 48.5% (n = 16) postoperative tumor recurrences overall. Disease-free survival was significantly shorter for tumor extension into or onto the hypopharynx (p = 0.041). Postoperatively, 72.7% of patients developed a pharyngocutaneous fistula, of which 24.2% required surgical treatment. The hospital stay was 28.0 ± 16.1 days. Conclusion: Salvage laryngectomy is associated with a high rate of treatable complications and high morbidity. Nevertheless, considering the advanced tumor stages treated, it allows for respectable oncological results.
CRIS-Team Scopus Importer:2021-04-23
Keywords: Laryngeal neoplasms; Postoperative complications; Recurrence; Salvage therapy; Treatment outcome

Simultaneous Application of Ultrasound and Sialendoscopy and its Value in the Management of Sialolithiasis - Koch, Michael; Schapher, Mirco; Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (Ultraschall in der Medizin, 2020)
Objective Ultrasound (US) and sialendoscopy (SE) are routinely used in patients presenting with sialolithiasis in the submandibular (SMG) and parotid gland (PG). The objective was to assess the value of the simultaneous application of US and SE in the management of sialolithiasis. Study Design Retrospective study. Setting: Tertiary referral center for salivary gland diseases. Participants: Patients in whom US and SE as single investigation tools were neither conclusive nor useful in the management of sialolithiasis were investigated using both methods simultaneously (simUS + SE). Main outcome measures: Establishment of the final diagnosis and/or contribution to the planning/performing of treatment in sialolithiasis. Results 74 patients were examined by simUS + SE (58.1 % SMG and 41.9 % PG). In all patients (unclear) hyperechoic reflexes were assessed and/or localized by SE-controlled US na-vigation. 68.9 % of the patients were investigated for diagnostic or differential-diagnostic reasons including distinguishing extraductal from intraductal calcifications and/or to exclude residual stones after therapy. In 52.7 % simUS + SE was used to plan and/or perform further treatment, in 20.3 % to enable performing a combined approach (all PG) and in 29.7 % to evaluate and plan the most adequate therapy (mainly intraductal vs. extracorporeal shock wave lithotripsy, 68.2 % of these SMG). In two cases SE-controlled and US-guided stone extraction was performed. Conclusion SimUS + SE is an innovative approach which proved to be very useful in managing sialolithiasis. It added valuable information regarding the establishment of a diagnosis or differential diagnosis, planning and performing the most adequate treatment, intraoperative control of therapy and postoperative follow-up.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Diagnosis; Salivary gland; Sialendoscopy; Therapy; Ultrasound

Simultaneous application of ultrasound and sialendoscopy: experience in the management of stenosis and other non-sialolithiasis-related salivary gland disorders - Koch, M.; Schapher, Mirco; Goncalves, Miguel; Iro, Heinrich; Mantsopoulos, K. (European Review for Medical and Pharmacological Sciences, 2020)
OBJECTIVE: To assess the value of the simultaneous application of ultrasound and sialendoscopy (US+SE) in several salivary gland diseases not caused either by sialolithiasis or by tumours. PATIENTS AND METHODS: US+SE are routinely used in patients with inflammatory, obstructive, and other non-tumorous major salivary gland diseases. In patients in whom US and SE as single investigation tools were not conclusive or not useful in the management of several non-sialolithiasis-related conditions (stenoses, ductal anomalies, ductal trauma, space-occupying paraductal lesions), both methods were used simultaneously for diagnosis and treatment. RESULTS: US+SE were used simultaneously in 44 patients for 56 indications. Stenosis was managed in 36 cases (81.8%) and in thirty-eight of the indications (67.9%) with simultaneous US+SE. The successful opening was achieved in 23 (63.9%), conservative and/or ablative treatment was indicated in 13 (36.1%), and further imaging was indicated in two (5.5%) of these cases. Post-traumatic or postinfectious complications were managed in 12 (27.3%) of all cases, and isolated ductal anomalies and paraductal space-occupying lesions were assessed in three cases (8.3%) each. In all instances, simultaneous US+SE clearly improved the management in diagnosis and/or therapy. CONCLUSIONS: Simultaneous application of US+SE provided additional information that proved to be valuable for diagnosis, planning, and treatment in several non-sialolithiasis-related conditions such as stenoses, ductal anomalies, ductal trauma, and space-occupying paraductal lesions.
CRIS-Team Scopus Importer:2020-03-31

Successful free flap salvage surgery with off-label use of Alteplase: A case report, review of the literature and our free flap salvage algorithm - Barhoum, Fatima; Tschaikowsky, Klaus; Koch, Michael; Kapsreiter, Markus; Sievert, Matti; Müller, Susanna; Goncalves, Miguel; Traxdorf, Maximilian; Scherl, Claudia (International Journal of Surgery Case Reports, 2020)
Introduction: Microvascular free tissue transfer is a technique for reconstruction of large defects in head and neck surgery. Failure due to microvascular thrombosis can lead to microvascular damage or flap loss. Recombinant tissue-type plasminogen activator (Alteplase) is still an off-label use but it can help to rescue free flaps when embedded in a salvage algorithm. Presentation of case: A 39-year-old patient with received a tumor resection and reconstruction by a radial forearm flap of the left palate. Postoperatively a venous flap thrombosis occurred and immediate surgical revision was done. Initially eperfusion of the flap could not be achieved even after mechanical removal of the thrombus. Then a thrombolysis with Alteplase, which was applied directly into the radial artery, was done. The flap was salvaged and is now completely integrated into the mucosa. Flap salvage procedure was performed according to our free flap salvage algorithm. Discussion: Thrombolysis with Alteplase for free flap salvage is not a common method. Pedicle thrombosis cannot be predicted. Important procedures during surgical intervention when thrombosis occurs are careful reopening, removal of thrombus, flushing with heparin. Since these procedures failed, surgeons decided to employ Alteplase to optimally rescue the flap. Conclusion: The present case shows that pharmacological thrombolysis with Alteplase is an effective ultima ratio in free flap salvage with venous thrombosis, although it is still considered offlabel use. Early detection of flap failure and a clear salvage algorithm are important for successful surgical revisions.
CRIS-Team Scopus Importer:2020-10-09
Keywords: Alteplase; Flap salvage with recombinant tissue-type plasminogen activator; Free flap salvage; Free flap salvage algorithm; Recombinant tissue-type plasminogen activator; Venous thrombosis

Systematic interpretation of confocal laser endomicroscopy: larynx and pharynx confocal imaging score Interpretazione sistematica dell’endomicroscopia confocale laser: punteggio endomicroscopico confocale laringeo e faringeo - Sievert, Matti; Mantsopoulos, Konstantinos; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Rupp, Robin; Aubreville, Marc; Stelzle, Florian; Oetter, Nicolai; Maier, Andreas; Iro, Heinrich; Goncalves, Miguel (Acta Otorhinolaryngologica Italica, 2022)
Objective. Development and validation of a confocal laser endomicroscopy (CLE) classification score for the larynx and pharynx. Methods. Thirteen patients (154 video sequences, 9240 images) with laryngeal or phar-yngeal SCC were included in this prospective study between October 2020 and February 2021. Each CLE sequence was correlated with the gold standard of histopathological ex-amination. Based on a dataset of 94 video sequences (5640 images), a scoring system was developed. In the remaining 60 sequences (3600 images), the score was validated by four CLE experts and four head and neck surgeons who were not familiar with CLE. Results. Tissue homogeneity, cell size, borders and clusters, capillary loops and the nu-cleus/cytoplasm ratio were defined as the scoring criteria. Using this score, the CLE experts obtained an accuracy, sensitivity, and specificity of 90.8%, 95.1%, and 86.4%, respectively, and the CLE non-experts of 86.2%, 86.4%, and 86.1%. Interobserver agreement Fleiss’ kappa was 0.8 and 0.6, respectively. Conclusions. CLE can be reliably evaluated based on defined and reproducible imaging features, which demonstrate a high diagnostic value. CLE can be easily integrated into the intraoperative setting and generate real-time, in-vivo microscopic images to demarcate malignant changes.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Classification system; Confocal laser endomicroscopy; Head and neck cancer; Larynx; Non-invasive histological imaging; Pharynx

The current value of quantitative shear wave sonoelastography in parotid gland tumors - Thimsen, Vivian; Goncalves, Miguel; Koch, Michael; Mantsopoulos, Konstantinos; Hornung, Joachim; Iro, Heinrich; Schapher, Mirco (Gland Surgery, 2021)
Background: The preoperative differentiation between salivary gland tumor entities using computed tomography, magnetic resonance imaging (MRI) and ultrasound ( US) is still limited. Biopsies are often regarded as indispensable for properly characterizing these various lesions. The aim of this study was to analyze the value of acoustic radiation force impulse (ARFI) sonoelastography as an US differentiation tool when examining parotid gland (PG) lesions.
CRIS-Team WoS Importer:2021-05-28

The value of transcutaneous ultrasound in the diagnosis of tonsillar abscess: A retrospective analysis - Sievert, Matti; Miksch, Malin; Mantsopoulos, Konstantinos; Goncalves, Miguel; Rupp, Robin; Müller, Sarina Katrin; Traxdorf, Maximilian; Iro, Heinrich; Koch, Michael (Auris Nasus Larynx, 2021)
Objective: To identify the appropriate treatment in the tonsillar region's infections, a distinction between tonsillitis with or without abscess formation is essential. Ultrasound proved to be a valuable method in identifying abscess formation in the head and neck region. However, no report described the assessment of the tonsil region. This study aims to determine the feasibility of transcervical ultrasound for abscess visualization in the palatal tonsillar region. Methods: Retrospective analysis of 354 patients presenting with clinical suspicion of tonsillar abscess to a tertiary referral center and university hospital. All patients received a transcervical ultrasound to establish a primary diagnosis. The existence of an abscess was confirmed by puncture and incision, or final tonsillectomy. If no abscess could be delineated, non-abscessing tonsillitis was supposed, and conservative primary therapy and closed follow-up examinations were performed. Results: After the first diagnostic ultrasound examination, in 257 cases (72.59%), the diagnosis of an abscess could be established, but in 97 cases (27.40%), due to missing abscess formation criteria, non-abscessing tonsillitis was documented. Overall, ultrasonography demonstrated an overall accuracy of 78.8% in this selected cohort. The sensitivity, specificity, PPV, and NPV after the first ultrasound examination were calculated with 75.1%, 88.6%, 94.6%, and 57.3%, respectively. Conclusion: The presented data confirm that an abscess formation due to tonsillitis can be detected by transcervical ultrasound, enabling prompt, adequate management. As transcervical ultrasound can be conducted fast and is not associated with radiation, it can be regarded as a first-line diagnostic tool in this condition.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Diagnostic; Intratonsillar abscess; Parapharyngeal abscess; Peritonsillar abscess; Tonsillar abscess; Transcutaneous ultrasound

Thrombose genähter vs. gekoppelter Anastomosen bei mikrovaskulären Kopf- und Halsrekonstruktionen - Sievert, Matti; Koch, Michael; Goncalves, Miguel; Richter, Daniel; Tamse, Rosalie; Müller, Sarina Katrin; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Harreus, Uli; Iro, Heinrich (Laryngo-Rhino-Otologie, 2020)
Objective The Anastomotic Coupling Device for microvascular anastomoses has become widely used in free tissue transplantation. This study compares the thrombosis rate and flap failure as a function of the anastomosis technique at a large head and neck cancer center. Material and Methods Retrospective analysis of all patients receiving free flap reconstructions in the period 2001-2019. Reconstruction type, recipient vessels, number of venous anastomoses, coupler size, and operation time were investigated. We compared the rates of venous thrombosis between hand sewn and coupled anastomoses, as well as the rate of flap failure. Results A total of 403 free flap reconstructions were performed for over 17 years. The venous anastomosis was sewn in 113 flaps in single suture technique, and in 290 cases, coupler device was used. The rate of venous thrombosis requiring immediate surgical revision was 6.2 % (7/113) in the sewn group compared to 7.6 % in the coupled group (22/290; p = 0.627). With an overall success rate of 95.0 % (383/403), the rate of flap failure was 3.6 % (4/113) and 5.5 % (16/290; p = 0.421), respectively. Surgical time is comparable with 680 ± 144 minutes in the hand-sewn group and 688 ± 167 minutes in the coupled group (p = 0.678). Conclusions With similar success rates, the coupler device is an effective alternative to venous anastomosis in single suture technique. Due to the generally low rate of pedicle thrombosis in both groups, we cannot separate the influence of the anastomosis technique from possible interfering variables.
CRIS-Team Scopus Importer:2020-10-02
Keywords: anastomotic coupling device; flap failure; free flap reconstruction; pedicle thrombosis; venous anastomosis

Transdermal scopolamine for the prevention of a salivary fistula after parotidectomy - Mantsopoulos, Konstantinos; Goncalves, Miguel; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2018)
Our aim was to investigate whether perioperative transdermal application of scopolamine could help to prevent fistulas after parotidectomy, and to this end we retrospectively studied the records of all patients (n=645) who had benign parotid tumours treated by partial parotidectomy between 2011 and 2016. We found that scopolamine led to a significant decrease in the incidence of salivary fistulas from 54/371(15%) in the group not given it to 10/274 (4%) in the group given it (p<0.0001). The "number needed to treat" was 9.17. There was a relatively low incidence of all adverse effects after scopolamine. Our results are encouraging. Thorough consideration of the contraindications and a knowledge of the potential adverse effects are crucial for its successful implementation.
EVALuna2:35391

Transferability of Deep Learning Algorithms for Malignancy Detection in Confocal Laser Endomicroscopy Images from Different Anatomical Locations of the Upper Gastrointestinal Tract - Aubreville, Marc; Goncalves, Miguel; Knipfer, Christian; Oetter, Nicolai; Würfl, Tobias; Neumann, Helmut; Stelzle, Florian; Bohr, Christopher; Maier, Andreas (Communications in Computer and Information Science, 2019)
Squamous Cell Carcinoma (SCC) is the most common cancer type of the epithelium and is often detected at a late stage. Besides invasive diagnosis of SCC by means of biopsy and histo-pathologic assessment, Confocal Laser Endomicroscopy (CLE) has emerged as noninvasive method that was successfully used to diagnose SCC in vivo. For interpretation of CLE images, however, extensive training is required, which limits its applicability and use in clinical practice of the method. To aid diagnosis of SCC in a broader scope, automatic detection methods have been proposed. This work compares two methods with regard to their applicability in a transfer learning sense, i.e. training on one tissue type (from one clinical team) and applying the learnt classification system to another entity (different anatomy, different clinical team). Besides a previously proposed, patch-based method based on convolutional neural networks, a novel classification method on image level (based on a pre-trained Inception V.3 network with dedicated preprocessing and interpretation of class activation maps) is proposed and evaluated. The newly presented approach improves recognition performance, yielding accuracies of 91.63% on the first data set (oral cavity) and 92.63% on a joint data set. The generalization from oral cavity to the second data set (vocal folds) lead to similar area-under-the-ROC curve values than a direct training on the vocal folds data set, indicating good generalization.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Confocal Laser Endomicroscopy; Head and neck squamous cell carcinoma; Transfer learning

Transoral ultrasound: a helpful and easy diagnostic method in obstructive salivary gland diseases - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (European Radiology, 2019)
• Transoral ultrasound is a simple technique, very helpful for the evaluation of obstructive diseases of the salivary glands. • It overcomes most of the limitations of transcutaneous ultrasound.
CRIS-Team Scopus Importer:2019-05-02

Transoral Ultrasound in the Diagnosis of Obstructive Salivary Gland Pathologies - Schapher, Mirco; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich; Koch, Michael (Ultrasound in Medicine and Biology, 2019)
Transcutaneous ultrasound (TCUS) is an accepted diagnostic method in salivary gland diseases. However, sparse data are available on the use of transoral ultrasound (TOUS) in sialadenopathies. One hundred five patients presenting with various obstructive sialadenopathies were examined using TOUS and TCUS. Ultrasound findings were validated by direct visualization in subsequent sialendoscopy examinations. By TOUS, but not by TCUS, all patients with sialolithiasis (70/105) could be identified and virtually all concrements, even very small ones, were detected and distinguished from artifacts. Ductal stenoses (16/105) could be correctly differentiated from sialoliths, and exceptional insights into the delicate anatomy of parotid duct stenoses were gained. TOUS provided detailed information on other space-occupying lesions (14/105) and circumvented the method-related diagnostic weaknesses of TCUS. As a valuable tool in the diagnosis of obstructive sialadenopathies, TOUS seems superior to TCUS in pathologies involving the distal parotid duct, the submandibular duct system and the floor of the mouth.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Obstructive sialadenopathy; Salivary duct stenosis; Salivary glands; Sialolithiasis; Transoral ultrasound

Ultrasound in the Assessment of Parotid Duct Stenosis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Journal of Ultrasound in Medicine, 2019)
Objectives Parotid duct stenosis may occur with or without accompanying ductal anomalies, with associated differences in their pathogenesis and management. By identifying the characteristics of a stenosis, ultrasound (US) can assist in tailored management of parotid duct stenosis. The objective of this study was therefore to describe the US characteristics of parotid duct stenoses and to evaluate criteria for whether and in what ways these can be distinguished from each other by using US. Methods A total of 108 patients who presented with parotid duct stenoses (130 parotid glands) were examined with high-resolution US between 2014 and 2017. The stenoses were assessed for duct dilatation, location, signs of ductal anomalies (circular encroachments/webs, duct bending/kinking, and presence of a megaduct) and the echogenicity of the gland parenchyma. Results Ultrasound was able to distinguish between stenoses associated with ductal anomalies and those without anomalies. Webs (82.5% versus 7.8%; P < .001), kinking (75.0% versus 3.3%; P < .001), and a megaduct (87.50% versus 15.63%; P < .001) and a tendency toward normal echogenicity in the gland parenchyma (77.5% versus 25.6%; P < .001) were significantly associated with ductal anomalies. Stenoses associated with ductal anomalies also had significantly larger duct diameters in comparison with those without anomalies (mean +/- SD, 9.19 +/- 3.65 versus 3.27 +/- 2.17 mm; P < .001). Conclusions This study describes US parameters that allow more detailed characterization of parotid stenoses with or without accompanying ductal anomalies. Differentiating between these at an early stage may be helpful for decision making on the further management in these patients.
CRIS-Team WoS Importer:2019-11-01

Ultrasound in the diagnosis of parotid duct obstruction not caused by sialolithiasis: diagnostic value in reference to direct visualization with sialendoscopy - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Dentomaxillofacial Radiology, 2021)
Objectives: The aim of this study was to evaluate the diagnostic value of ultrasound in the obstructive pathology of the parotic gland not caused by sialolithiasis using sialendoscopy as reference standard.
CRIS-Team WoS Importer:2021-03-26

Ultrasound Supplemented by Sialendoscopy: Diagnostic Value in Sialolithiasis - Goncalves, Miguel; Mantsopoulos, Konstantinos; Schapher, Mirco; Iro, Heinrich; Koch, Michael (Otolaryngology-Head and Neck Surgery, 2018)
Objective To assess the value of ultrasound, if indicated, supplemented by sialendoscopy, in the diagnosis of sialolithiasis. Study Design Retrospective study. Setting Referring center for salivary gland diseases. Subjects and Methods All patients who presented with a suspected diagnosis of obstructive sialopathy between January 2011 and April 2017 and had not undergone any treatment were retrospectively evaluated. A total of 2052 patients and 2277 glands were included in the study. Ultrasound examinations were carried out initially and followed by sialendoscopy in all cases. Direct demonstration of sialothiasis by sialendoscopy, transoral ductal surgery, and discharge of concrements/observation of fragments during sialendoscopy after extracorporeal shock-wave lithotripsy were regarded as definitive evidence of sialolithiasis. Results Ultrasound had an accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of 94.77%, 94.91%, 94.57%, 96.14%, and 92.89%, respectively, for the diagnosis of sialolithiasis. All false-positive findings were correctly diagnosed, and in all false-negative findings, stones/fragments were visualized by sialendoscopy. Over 95% of the false-negative findings in major salivary glands (64/67) had visible ductal dilation in sonography, and in 73.1%, the stones not detected on ultrasound were located in the distal part of the duct, which is easily accessible with the sialendoscope. Conclusion This study shows that sialolithiasis can be diagnosed using ultrasonography with a high degree of certainty. If supplemented by sialendoscopy, the correct diagnosis could be established in virtually all cases of sialolithiasis. Ultrasound supplemented by sialendoscopy has the potential to serve as an alternative diagnostic standard in the future.
EVALuna2:35387

Watchful waiting in carefully selected metachronous cystadenolymphomas of the parotid gland: a reliable option? - Mantsopoulos, K.; Goncalves, Miguel; Koch, M.; Iro, Heinrich (British Journal of Oral and Maxillofacial Surgery, 2019)
The aim of this study was to evaluate the potential of watchful waiting in the treatment of metachronous cystadenolymphomas, taking the experience of our department into consideration. All patients suspected of having a metachronous cystadenolymphoma, and who had a minimum follow-up time of 12 months, were studied (n = 26). Data about the growth rate, number of lesions, and symptoms of inflammation were recorded. Mean (range) follow-up was 36 (13–94) months. Metachronous tumours developed in three cases on the ipsilateral side, in 22 cases on the contralateral side, and on both sides in one case. The mean rate of growth /lesion was 15% /year (range: 22%–158%). There were no signs of local inflammation. The extreme variability in the behaviour of metachronous cystadenolymphomas points to the need for an individualised approach, accurate investigation of the sonographic characteristics, and continuous watchful waiting in affected patients.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Benign tumours; Cystadenolymphoma; Parotid gland; Warthin tumour; Watchful waiting